1995
DOI: 10.1016/0009-9236(95)90168-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of absorption and first-pass gut and hepatic metabolism in humans: Studies with cyclosporine*

Abstract: The low and variable bioavailability of cyclosporine has been attributed to poor absorption. However, recent studies have suggested that intestinal first-pass metabolism exerts a significant effect on bioavailability. We describe theory and methods to differentiate the contribution from oral absorption and intestinal and hepatic metabolism to overall cyclosporine bioavailability. Analysis of data from previous studies in our laboratories shows that in the absence of intestinal metabolism, cyclosporine absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
189
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(201 citation statements)
references
References 9 publications
(1 reference statement)
8
189
2
2
Order By: Relevance
“…On the other hand, CYP3A accounts for about 30 and 70% of total CYP activity in the liver and small intestine, respectively [12][13][14], and intestinal first-pass metabolism mediated by CYP3A has been shown to be clinically relevant for several drugs, including cyclosporin A [15,16]. However, it remains to be fully clarified whether P-gp and/or CYP3A controls the oral bioavailability of cyclosporin A by limiting absorption from the small intestine.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…On the other hand, CYP3A accounts for about 30 and 70% of total CYP activity in the liver and small intestine, respectively [12][13][14], and intestinal first-pass metabolism mediated by CYP3A has been shown to be clinically relevant for several drugs, including cyclosporin A [15,16]. However, it remains to be fully clarified whether P-gp and/or CYP3A controls the oral bioavailability of cyclosporin A by limiting absorption from the small intestine.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Enterocytes have a variety of structural features, including tight junctions reducing paracellular permeability, numerous drug transporters, and a set of metabolic enzymes that may all affect the entry of drugs into the body. The extent to which a drug is absorbed also depends on the intrinsic properties of the compound such as solubility, permeability, efflux or uptake transport properties, and susceptibility to metabolic degradation (Martinez and Amidon, 2002;Benet et al, 2004).Although the liver is known as the major site of first-pass extraction, recent studies have indicated that the small intestine also contributes significantly to the first-pass metabolism of many drugs, e.g., cyclosporine (Wu et al, 1995), nifedipine (Iwao et al, 2002), midazolam (Paine et al, 1996, and diltiazem (Iwao et al, 2004). It is known that several uptake and efflux transporter and P450 isoforms are expressed in the human and rat intestine (van de Kerkhof et al, 2007).…”
mentioning
confidence: 99%
“…Although the liver is known as the major site of first-pass extraction, recent studies have indicated that the small intestine also contributes significantly to the first-pass metabolism of many drugs, e.g., cyclosporine (Wu et al, 1995), nifedipine (Iwao et al, 2002), midazolam (Paine et al, 1996), and diltiazem (Iwao et al, 2004). It is known that several uptake and efflux transporter and P450 isoforms are expressed in the human and rat intestine (van de Kerkhof et al, 2007).…”
mentioning
confidence: 99%
“…[24][25][26] Wu et al reported that the extraction ratio for orally administered cyclosporine in the gut is approximately 2-fold higher than that in the liver in kidney transplant patients. 24) Hebert reported that tacrolimus is metabolized primarily by CYP3A4 in the liver and small intestine. 25) In addition, Paine et al reported that intestinal CYP3A4 contributes to the first-pass metabolism of midazolam in liver transplant patients.…”
Section: Resultsmentioning
confidence: 99%